2023
DOI: 10.3390/land12071448
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land Ecological Security from 2000 to 2020 in the Chengdu Plain Region of China

Abstract: The purpose of land ecological security (LES) assessment is to evaluate the influence of land use and human activities on the land ecosystem. Its ultimate objective is to offer decision-making assistance and direction for safeguarding and rejuvenating the well-being and effectiveness of the land ecosystem. However, it is important to note that there are still significant uncertainties associated with current land ecological safety assessments. This paper presents a comprehensive evaluation model that combines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The reason is that the plain area is relatively rich in resources that are easy to obtain, population and industrial agglomeration lead to the excessive consumption of resources and environmental damage, and the large-scale expansion of construction land undermines the stability of the original regional ecosystem, having a negative impact on ecosystem services. This is consistent with the results obtained by Zhang et al using the pressure-state-response (PSR) framework [25]. In addition, the ecosystem service index in the plain area showed a spatial distribution of low in the middle and high in the periphery, and the ecosystem type in the plain area was relatively simple, while the regional self-regulation ability and the ability to resist human disturbance were poor.…”
Section: Impacts Of Urbanization On Ecosystem Services In Plain Areassupporting
confidence: 91%
See 1 more Smart Citation
“…The reason is that the plain area is relatively rich in resources that are easy to obtain, population and industrial agglomeration lead to the excessive consumption of resources and environmental damage, and the large-scale expansion of construction land undermines the stability of the original regional ecosystem, having a negative impact on ecosystem services. This is consistent with the results obtained by Zhang et al using the pressure-state-response (PSR) framework [25]. In addition, the ecosystem service index in the plain area showed a spatial distribution of low in the middle and high in the periphery, and the ecosystem type in the plain area was relatively simple, while the regional self-regulation ability and the ability to resist human disturbance were poor.…”
Section: Impacts Of Urbanization On Ecosystem Services In Plain Areassupporting
confidence: 91%
“…To date, a large number of studies have explored the horizontal and regional differentiation characteristics of urbanization's impact on ecosystem services through data description and quantitative analyses [17][18][19][20][21][22][23][24] and have proven that altitude factors may have potential impacts on urbanization and ecosystem services [25][26][27][28][29], but the specific law of urbanization's impact on ecosystem services under altitude gradient is still unclear. However, studies have shown that mountains account for up to 33% of the world's land area and are home to 26% of the world's population, 27% of which is urban [5].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that government implementation programs on land issues have the highest impact on the quality of land resource security. Regions in the three northeastern provinces should formulate relevant land resource protection policies to adjust for the negative socioeconomic and natural environmental pressures on land resources, establish a sustainable land resource environment, formulate land ecology safeguard policies in accordance with the current status of local land ecology, strengthen environmental protection efforts, further optimize the industrial structure while improving economic development and residents' income, enhance energy conservation and emission reduction, reduce pollutant generation and emission, raise awareness of environmental protection, and reduce waste discharge [29,30]. Establish early warning and protection mechanisms against natural disasters, strengthen protection measures against soil erosion and other natural disaster, encourage the continuous and profitable use of land, increase the resilience of land ecosystems to natural calamities, and better achieve improved ecological land security in the three northeastern provinces.…”
Section: Ranking Of Factors Affecting Land Ecological Securitymentioning
confidence: 99%
“…Lastly, economic benefits are also an important goal of human-land relationships in rural areas, and the income brought by land is a key factor in measuring whether it can retain farmers. If the income brought by land can offset the cost and have a certain surplus, it can promote the human-land relationship to some extent [34]. Farmers invest a lot of time, labor, and equipment, and the output and benefits of land must meet certain standards, satisfy farmers' living expenses, and be economically feasible, so that rural areas can retain famers.…”
Section: Evaluation Standard Evaluation Index Weightmentioning
confidence: 99%